2015
DOI: 10.5897/ajps2014.1244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed control methods on weed density and maize (Zea mays L.) yield in west Shewa Orimia, Ethiopia

Abstract: ), however, non-significant difference existed among them in Guder, whereas the highest was observed in weedy check (170.93, 382.13 gm -2 ) in Guder and Ambo, respectively. Moreover, those treatments also significantly increased the yield and yield component of maize in both locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
4
4
0
4
Order By: Relevance
“…Il y'a une différence très hautement significative (P < 0,001). Ces résultats sont similaires à avec ceux de Tesfay et al (2015) [43] en Ethiopie qui ont constaté que les épis de maïs qui ont subi l'action des adventices ont présenté une circonférence et une longueur plus petite comparés aux épis des parcelles qui ont été désherbées. En effet, les adventices étant en compétition avec A. esculentus pour les éléments nutritifs et la lumière, cela entraine la formation des fruits de petite taille ainsi que de circonférence réduite.…”
Section: Phase De Fructificationunclassified
See 2 more Smart Citations
“…Il y'a une différence très hautement significative (P < 0,001). Ces résultats sont similaires à avec ceux de Tesfay et al (2015) [43] en Ethiopie qui ont constaté que les épis de maïs qui ont subi l'action des adventices ont présenté une circonférence et une longueur plus petite comparés aux épis des parcelles qui ont été désherbées. En effet, les adventices étant en compétition avec A. esculentus pour les éléments nutritifs et la lumière, cela entraine la formation des fruits de petite taille ainsi que de circonférence réduite.…”
Section: Phase De Fructificationunclassified
“…[35] ont montré que les fruits de A. esculentus ont un poids plus petit dans le traitement où les adventices n'ont pas été contrôlées. En Ethiopie, les travaux effectués par Tesfay et al (2015) [43] montrent que les épis de maïs ont moins de graines lorsque la culture est abandonnée aux adventices. Ces résultats sont aussi similaires à ceux de Sadak et al (2013) [36] qui ont montré que le gombo cultivé en présence des substrats issus du compost a un impact positif sur le rendement en fruits de A. esculentus.…”
Section: Rendements En Fruits Et En Grainesunclassified
See 1 more Smart Citation
“…Different weed control methods have been utilized to manage weeds; mechanical and chemical methods are more frequently used than any other methods (Tesfay et al, 2015). Meanwhile, none of the two methods has satisfactorily provided season long effect on weed control when used alone (Badmus et al, 2006;Lagoke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The reports of Tesfay et al (2015) had identified grasses, broadleaved and sedges to be the major weed categories in maize plots. Owing to the awareness that functional interactive complexes exist among different weed species and soil characteristics, climate, cultural practices and different weed control methods (Kremer, 2004), a kin look at the prospective roles of different weed categories on yield and yield components of corn in Ikole-Ekiti, Southwestern Nigeria was thought worthwhile to assess the relative scoring of the negative potentials of the different weed types.…”
Section: Introductionmentioning
confidence: 99%